1992
DOI: 10.1128/jb.174.12.4157-4165.1992
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of a major polymorphic tandem repeat in Mycobacterium tuberculosis and its potential use in the epidemiology of Mycobacterium kansasii and Mycobacterium gordonae

Abstract: In this study, the occurrence of repeated DNA sequences in the chromosome of Repetitive DNA sequences have also been found in mycobacteria. The insertion elements IS900 from Mycobacterium paratuberculosis (4, 12), IS901 from Mycobacterium avium (19), IS1096 from Mycobacterium smegmatis (2), IS1081 from Mycobacterium bovis, and the IS3 family of insertion elements present in the species of the Mycobacterium tuberculosis complex (15,22,37) are present in multiple copies in the mycobacterial chromosome (16,40).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
114
0

Year Published

1998
1998
2008
2008

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 137 publications
(117 citation statements)
references
References 45 publications
2
114
0
Order By: Relevance
“…The PGRS encodes the motif AsnGlyGlyAlaGlyGlyAla, or variants thereof, while MPTR encodes Asn-X-Gly-X-Gly-Asn-X-Gly. Multiple tandem repetitions of these motifs are found in the corresponding proteins, which are acidic and exceptionally rich in glycine, and at the gene level variations occur in the repeat copy number and sequence thereby accounting for the genomic polymorphisms observed in hybridization patterns obtained with PGRS or MPTR probes (Hermans et al, 1992 ;Poulet & Cole, 1995a, b ;van Soolingen et al, 1993). Initially, the PGRS and MPTR sequences were thought to correspond to dispersed tandem repeats or microsatellites but the finding that they were part of coding sequences led to reflection about the functions of these proteins.…”
Section: The Pe and Ppe Gene Familiesmentioning
confidence: 99%
“…The PGRS encodes the motif AsnGlyGlyAlaGlyGlyAla, or variants thereof, while MPTR encodes Asn-X-Gly-X-Gly-Asn-X-Gly. Multiple tandem repetitions of these motifs are found in the corresponding proteins, which are acidic and exceptionally rich in glycine, and at the gene level variations occur in the repeat copy number and sequence thereby accounting for the genomic polymorphisms observed in hybridization patterns obtained with PGRS or MPTR probes (Hermans et al, 1992 ;Poulet & Cole, 1995a, b ;van Soolingen et al, 1993). Initially, the PGRS and MPTR sequences were thought to correspond to dispersed tandem repeats or microsatellites but the finding that they were part of coding sequences led to reflection about the functions of these proteins.…”
Section: The Pe and Ppe Gene Familiesmentioning
confidence: 99%
“…Orf6 possesses an N-terminal hydrophobic segment consistent with a lipoprotein signal sequence. Orf6 also has similarity to part of the 1D sequence located in the RD1 region of M. bovis and M. tuberculosis (Mahairas et al, 1996). RD1 is a 9.5 kb DNA segment that is found in virulent laboratory and clinical isolates of M. bovis the fragment that was close to a series of eight 10 bp sequences with some similarity to major polymorphic tandem repeat (MPTR) sequences (Hermans et d.,…”
Section: Characteristics Of the 8cg 2405 Bp Fragmentmentioning
confidence: 99%
“…The MPTR consists of 15-bp repeats with a single consensus sequence but with substantial sequence variability between adjacent repeats (Hermans et al, 1992). We amplified the 48 strains in our panel in five MPTR loci, including four published loci (Hermans et al, 1992;Shinnick, 1987) and one locus identified by our search of cosmid sequences.…”
Section: Mptr Locimentioning
confidence: 99%
“…We amplified the 48 strains in our panel in five MPTR loci, including four published loci (Hermans et al, 1992;Shinnick, 1987) and one locus identified by our search of cosmid sequences. One of these MPTR loci (MPTR-A) demonstrated length polymorphism, corresponding to 15,16 or 17 copies of the 15-bp repeat unit (Tables 2 and 3).…”
Section: Mptr Locimentioning
confidence: 99%